2015
DOI: 10.1007/s11418-015-0918-4
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B induces DNA damage and autophagy mediated by reactive oxygen species (ROS) in MCF-7 breast cancer cells

Abstract: Cucurbitacin B (Cuc B), a natural compound extracted from cucurbitaceous plants, demonstrated potent anticancer activities, while the underlying mechanisms remain unclear. We investigated the anticancer effect of Cuc B on MCF-7 breast cancer cells. Cuc B drastically decreased cell viability in a concentration-dependent manner. Cuc B treatment caused DNA damage, as shown by long tails in the comet assay and increased γH2AX protein expression. Immunofluorescence staining showed that Cuc B treatment induced nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 47 publications
1
29
0
1
Order By: Relevance
“…Increased LDH release suggested that Cuc B might affect cell membrane. We previously reported that Cuc B induced DNA damage in A549 [27], K562 [23], and MCF-7 cells [28]. Cuc B induced long tails in comet assay and increased γ -H 2 AX expression suggesting that it induced DNA damage in BEL-7402 cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Increased LDH release suggested that Cuc B might affect cell membrane. We previously reported that Cuc B induced DNA damage in A549 [27], K562 [23], and MCF-7 cells [28]. Cuc B induced long tails in comet assay and increased γ -H 2 AX expression suggesting that it induced DNA damage in BEL-7402 cells.…”
Section: Discussionmentioning
confidence: 99%
“…MDC staining used to detect the formation of acidic vesicular organelles in Cuc B-treated cells was performed as in our previous reports [28, 34]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations